Ukrainian Refugees in Germany: Evidence From a Large Representative Survey - Brücker, Herbert; Ette, Andreas; Grabka, Markus M.; Kosyakova, Yuliya; Niehues, Wenke; Rother, Nina; Spieß, C. Katharina; Zinn, Sabine; Bujard, Martin; Cardozo Silva, Adriana R.; Décieux, Jean Philippe; Maddox, Amrei; et al. (Comparative population studies, 2023)
This study describes the first wave of the IAB-BiB/FReDA-BAMF-SOEP Survey on Ukrainian Refugees in Germany, a unique panel dataset based on over 11,000 interviews conducted between August and October 2022. The aim of the IAB-BiB/FReDA-BAMF-SOEP Survey is to provide a data-infrastructure for theory-driven and evidence-based research on various aspects of integration among Ukrainian refugees in Germany, the second most important destination country in the EU after Poland, hosting over a million people who arrived in Germany shortly after the Russian invasion of Ukraine. Based on the survey, this study also provides first insights into demographic, educational, linguistic, occupational, and social characteristics of this population. The analyses revealed that the refugee population comprised mostly young and educated individuals, with a significant proportion of females without partners and female-headed separated families. While German language skills were limited, about half of Ukrainian refugees had attended or were attending language courses. However, the integration process faced significant challenges, as the participation of children in day-care was relatively low, and the self-reported life satisfaction was markedly below the average of the German population. The study highlights the need for targeted policy measures to address such issues. Additionally, policies may aim at harnessing the high potential of the Ukrainian refugees for the German labor market. Given that a substantial proportion would like to stay in Germany permanently, policymakers should take note of these findings and aim to facilitate their long-term integration process to ensure that these refugees may thrive in Germany.